Pengaruh Corporate Social Responsibility, Political Connection, Financial Performance, terhadap Reputasi Perusahaan dengan Agresivitas Pajak sebagai Variabel Modersting - Riska Mawarni; Rio Johan Putra (Universitas 17 Agustus 1945 Jakarta, 2023)
This study aims to examine the effect of Corporate Social Responsibility, Political Connection, and Financial Performance on Company Reputation with Tax Aggressiveness as a moderating variable. Secondary data used in this study through data collection available on the Indonesian Stock Exchange website in the form of annual financial reports. The main population used in this study are companies registered on JII for the 2017-2021 period, where the sampling method is used. The results of this study indicate that corporate social responsibility has a positive effect on company reputation, political connections have a negative effect on company reputation, financial performance has a positive effect on company reputation, tax aggressiveness has a positive effect on company reputation, moderation of tax aggressiveness weakens the effect of corporate social responsibility on reputation. firms, moderation of tax aggressiveness strengthens the effect of political connections on corporate reputation, and moderation of tax aggressiveness strengthens the effect of financial performance on corporate reputation.